Incidence Of Postpartum Metritis In Surti Buffaloes In Amul Milk Shed Area Of Gujarat - Patil, R.D.; Patel, J.A.; Patel , S.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
The incidence of metritis in dairy bovines of Amul milk shed area of Anand for the year 2009-10 was recorded as 17.34 % of the total reproductive disorders (24595) and as 0.78 % of the total clinical cases (540416) attended. The highest incidence of metritis was noticed during monsoon (42.07 %) followed by winter (35.98 %) and the least in summer (21.95 %). The incidence of metritis had a close positive association with the calving rate and THR - a climatic component, suggesting that peripartum care and calving hygiene apart from elevating climatic and production stress can reduce the incidence of postpartum metritis and thereby the economic loss to the farmers.
Keywords: Buffaloes; Reproductive disorders; Metritis; Incidence; Amul milk shed area